Field notes contributed by Eugene and Eloise Armstrong, November 28, 1984 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1984)
Field notes were contributed by Eugene and Eloise Armstrong, November 28, 1984. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed